PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GOOGLE SITES PADA PEMBELAJARAN IPS DI KELAS V SEKOLAH DASAR - Sari, Karmila; Amus, Sunarto; Zulnuraini; Herlina; Nasrullah (JS (JURNAL SEKOLAH), 2025)
Abstract: The purpose of this research is to describe the process of developing Google Sites-based learning media for Social Studies Learning in Class V at Inpres Baliase Elementary School and to determine the effectiveness of the developed media. This study employed a Research and Development (R&D) approach using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 18 Class V students at Inpres Baliase Elementary School. The instruments used included validation sheets from media and material experts, student and teacher response questionnaires, as well as Pretes and Posttes assessment. The validation results showed that the Google Sites-based learning obtained a score of 94,6% from media experts and 96% from material experts, indicating that the media was high valid. The effectiveness test result revealed an increase in the average Pretes score from 55,78 to 88.00 in the Posttes, with an average N-Gain value 0f 0,72, which falls into high category indicating that the media is effective. In addition, student response questionnaires showed 96,6% and teacher response 81,2%, indicating that the Google Sites-based learning media is considered highly attractive.   Keyword: Learning Media, Google Sites, Social Studies Learning, ADDIE, Learning Effectiveness   Abstrak: Tujuan Penelitian ini adalah untuk mendeskripsikan proses pengembangan media pembelajaran berbasis Google Sites pada pembelajaran IPS dikelas V sekolah Dasar Inpres Baliase, dan mengetahui keefektifan media pembelajaran berbasis Google Sites. Penelitian ini menggunakan metode Research and Development (R&D) dengan model pengembangan ADDIE yang terdiri dari lima tahapan yaitu, Analysis, Design, Development, Implementation, dan Evalution. Subjek penelitian terdiri dari 18 siswa kelas V b SD Inpres Baliase. Instrumen yang digunakan meliputi lembar validasi dari ahli media, ahli materi, angket respon siswa dan juga guru serta tes Pretes dan Posttes. Hasil validasi menunjukkan bahwa media pembelajaran berbasis Google Sites memperoleh presentase 94,6% dari ahli media dan 96% dari ahli materi, sehingga dinyatakan sangat valid. Hasil uji efektivitas menunjukkan adanya peningkatan rata-rata nilai pretest sebesar 55,78 menjadi 88,00 pada Posttest dengan nilai rata-rata N-Gain sebesar 0,72 yang termasuk dalam kategori tinggi, sehingga media dinyatakan efektif. Selain itu, hasil angket respon siswa sebesar 96,6% dan respon guru sebesar 81,2% menujukkan bahwa media pembelajaran berbasis Google Sites ini tergolong sangat menarik Kata Kunci: Media Pembelajaran, Google Sites, Pembelajaran IPS, ADDIE, Efektivitas Pembelajaran.